PEMBAYARAN ELEKTRONIK NON-BANK DAN KONTRIBUSINYA TERHADAP AKUNTABILITAS PADA UMKM DI KOTA MATARAM - Nina Karina Karim; Siti Atikah; Indria Puspitasari Lenap (Indonesian Publication Center, 2021)
Advances in technology have changed the way we do our daily activities. Cell phones and tablets are not only used as a means of communication and information dissemination but also as portals that are used for shopping, completing banking transactions and even participating in the stock exchange. With the increasingly affordable prices of these devices, and the easier it is for people to access the internet, more and more businesses are turning to smart devices instead of spending money to buy conventional cash registers to help their business operations. The availability of various applications that can be run with smart devices also affects the way a company runs its business. This study seeks to see what factors influence the consideration of using a non-bank electronic payment system and its contribution to business accountability in MSMEs in Mataram City. The results of research on 25 companies classified as MSMEs in Mataram City show that the factors that influence companies to use non-bank electronic payment modes are more directed to business characteristics and the wishes of business owners, not to customer characteristics, choices of other payment modes and benefits of payment modes other. In addition, the use of non-bank electronic payment modes has not been found to be beneficial for business accountability.